Manufacturers satisfaction on third party logistics service quality: Malaysia perspective / Abdul Khabir Rahmat - Rahmat, Abdul Khabir (Institute of Graduate Studies, UiTM, 2018)
Little is known about how customer satisfaction was formed among users of logistics service in collectivist society particularly in Malaysia. Numbers of a study conducted in western countries which identified the elements contributing to satisfaction, the difference of cultural background between individualistic country and the collectivist country may suggest variations on how collectivist society value the element of logistics service and how they derive maximum satisfaction. In National Culture study conducted by Hofstede (2010) indicates that there is a difference of character/ preferences/ sensitivities between the individualistic and collectivist society. Therefore the objectives of the study are to investigate on what makes the users of logistics service satisfied among the collectivist society. Qualitative research was deployed. Preliminary data collection were conducted, five companies were interviewed for preliminary studies. Three companies are logistics providers, and two is logistics users. Preliminary results show that there are new elements which are not mentioned in any Logistics Service Quality previous works and 3PL reports that they need to know more about what makes their customer satisfied, which became the primary motivation to delve further into the study. The next step is the collection of primary data…